Tradisi Pembacaan Surah al-Kahfi di Pesantren Tebuireng: Analisis Fenomenologi Sosial Alfred Schutz - Muhammad Fatkhun Niam; Amrulloh Amrulloh (Tadabbur: Jurnal Integrasi Keilmuan, 2026)
The tradition of reciting Surah al-Kahfi has long been practiced within Indonesian Islamic boarding schools (pesantren) as an expression of religious devotion rooted in the Prophet’s hadith. Beyond its ritual dimension, the tradition represents the reception and actualization of hadith in the socio-religious life of pesantren communities. This study examines the tradition of reciting Surah al-Kahfi at Pesantren Tebuireng through the perspective of Alfred Schutz’s social phenomenology within the framework of living hadith. Employing a qualitative phenomenological approach, data were collected through participant observation, in-depth interviews, and documentation, then analyzed using Schutz’s concepts of because motive and in-order-to motive. The findings indicate that the tradition reflects the internalization of religious values shaped by collective experience, spiritual belief, and institutional culture. The recitation not only strengthens individual spirituality but also reinforces collective religious consciousness, enabling the hadith to function as a living social practice that is continuously interpreted, preserved, and transmitted within the pesantren tradition.